2002
DOI: 10.1097/00007632-200204010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Spindle Distribution, Morphology, and Density in Longus Colli and Multifidus Muscles of the Cervical Spine

Abstract: The current study examined spindle characteristics for an intrinsic neck muscle pair whose coactivation contributes to segmental stability of the cervical spine. The distribution and morphology of muscle spindles differ between the longus colli and the multifidus. In addition, these muscles have significant differences in terms of mean spindle density. Spindle characteristics represent one of many factors that govern proprioceptive regulation in skeletal muscle, and in neck muscles, the central connectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
170
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(183 citation statements)
references
References 48 publications
6
170
0
7
Order By: Relevance
“…The deep cervical muscles (longus colli, longus capitis, semispinalis cervicis, and multifidus) have a large muscle spindle density, segmental attachments, and high proportion of slow twitch fibers, and the main function is to guide and support vertebral motion segments (Jull et al, 2008a, Boyd-Clark et al, 2001. The large density of muscle spindles in the cervical muscles especially in the craniocervical region provides sensory information through connections with the visual, vestibular, and postural control systems (Treleaven, 2008b, Boyd-Clark et al, 2002, Kulkarni et al, 2001). …”
Section: Structure and Function Of Cervical Muscles In Neck Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep cervical muscles (longus colli, longus capitis, semispinalis cervicis, and multifidus) have a large muscle spindle density, segmental attachments, and high proportion of slow twitch fibers, and the main function is to guide and support vertebral motion segments (Jull et al, 2008a, Boyd-Clark et al, 2001. The large density of muscle spindles in the cervical muscles especially in the craniocervical region provides sensory information through connections with the visual, vestibular, and postural control systems (Treleaven, 2008b, Boyd-Clark et al, 2002, Kulkarni et al, 2001). …”
Section: Structure and Function Of Cervical Muscles In Neck Painmentioning
confidence: 99%
“…The abundance of mechanoreceptors in the cervical spine is important for maintaining postural control (Boyd-Clark et al, 2002), and altered proprioceptive input to reflex and/or voluntary control is thus a potential mechanism for disturbed postural control (Treleaven, 2008a, Wrisley et al, 2000. Neck pain is associated with impaired postural control characterized by greater postural sway and postural instability , Field et al, 2008, Cheng et al, 2015a.…”
Section: Postural Swaymentioning
confidence: 99%
“…This is reflected by the abundance of muscle spindles and mechanoreceptors located within the joint capsules, ligaments and paraspinal musculature. This is especially true of the suboccipital musculature which possess around 200 spindles/g of muscle (Boyd-Clark, Briggs, & Galea, 2002;Kulkarni, Babu, & Chandy, 2001). By comparison, the first lumbrical in the thumb contains a mere 16 spindles/g of muscle, and the gluteus maximus contains a mere 0.8 spindles/g (Liu, Thornell, & Pedrosa-Domellöf, 2003;Treleaven, 2008a).…”
Section: The Proprioceptive Properties Of the Cervical Regionmentioning
confidence: 99%
“…It is also possible that the fatty alterations in the deep suboccipital and extensor muscles, which are rich in muscle spindle density [4,5,34], may account for some of the common functional impairments observed in whiplash, such as kinesthetic deficits [22,31,32] and balance loss [17,60]. Previous studies have shown that subjects with whiplash who complain of dizziness demonstrate greater deficits in cervical JPE, neck influenced eye movement control, and postural stability when compared to those not complaining of these symptoms and when compared to healthy controls [32,58,59].…”
Section: Discussionmentioning
confidence: 99%